ULÍWMA BILIM BERIW MEKTEPLERINDE KLASSTAN TÍSQARÍ JUMÍSLARDÍ SHÓLKEMLESTIRIWDIŃ AYÍRÍM MÁSELELERI - Qurmanov, A.; Shamuratova, T.; Amanbaev, M.; Yuldasheva, N. (SCIENCE and SOCIETY, 2020)
The article deals with the education of the young generation in order to prepare highly educated specialists with the help of the effective organization of out-of-class work in secondary educational schools.